2011
DOI: 10.1139/l10-107
|View full text |Cite
|
Sign up to set email alerts
|

New formula for the estimation of shear resistance of fibre reinforced beams

Abstract: The paper presents an improved, fracture-mechanics-based formula for estimation of the ultimate shear resistance of steel fibre reinforced concrete beams. The proposed formula was evaluated using 312 published and 28 new test results and its accuracy was compared with 12 already known formulas. Twenty eight tests on reinforced concrete beams subjected to non-symmetrically placed concentrated loads were carried out, in which two different types of steel fibres: short straight and long hooked-end were used. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…An effective method to increase shear resistance of a structure element is to use steel fibres. It was found that the incorporation of an appropriate amount of steel fibres can enhance the shear capacity of reinforced concrete (RC) beams and slabs [16][17][18][19][20][21][22][23]. The steel fibres can also help to shift the failure pattern of structural elements from brittle shear mode to a more ductile flexural mode [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An effective method to increase shear resistance of a structure element is to use steel fibres. It was found that the incorporation of an appropriate amount of steel fibres can enhance the shear capacity of reinforced concrete (RC) beams and slabs [16][17][18][19][20][21][22][23]. The steel fibres can also help to shift the failure pattern of structural elements from brittle shear mode to a more ductile flexural mode [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, due to their disproportionately small size compared to stirrups, steel fibres can be more uniformly distributed in the concrete matrix, which results in a better bridging effect over the cracks throughout the entire concrete matrix. Secondly, the tensile strength of the concrete matrix can be improved with the presence of fibres, which can enhance the cracking shear force capacity of a structural element [20,28]. Despite the aforementioned merits of using steel fibres, there are limited published research efforts quantifying the effects of incorporating steel fibres on the behaviour of deep beams [11,12,[29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations of reinforced concrete (RC) beams in shear or RC slabs in punching shear have proven that using an adequate dosage of steel fibers of appropriate shapes can significantly enhance the shear loading capacity of the structures thanks to a good crack control mechanism provided by the steel fibers [10][11][12][13][14][15][16][17]. Adding the steel fibers to concrete may also result in the change from a brittle shear failure mode to a ductile flexure mode [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This small spacing is greatly advantageous since the fibers can offer a better crackbridging effect throughout the entire concrete matrix. The second benefit could be that deploying a sufficient amount of steel fibers can increase the tensile strength of the concrete matrix, which improves the shear-cracking resistance of the member [14]. Despite these evident benefits, up to now, relatively few works dealing with the use of steel fibers in deep beams have been published [8,[22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Steel plates of 200 mm wide and 100 mm wide were used at the loading point and support. The non-study region of the deep beam is strengthened by providing the shear reinforcement of 0.5% [53][54][55][56][57] as shown in Figure 4. One side of the beam was reinforced with stirrups to ensure that the failure of the beam occurs in the study region so that detailed instrumentation including DIC could be focused on that region.…”
Section: Test Specimen Detailsmentioning
confidence: 99%